PENDIDIKAN KRITIS DAN REKONSTRUKSI KURIKULUM MADRASAH - Hendri Purbo Waseso (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstractThis paper reveals the importance of the madrasah curriculum development through various contextual perspectives. Study of critical education occupies a position on a learner awareness efforts about the importance of continuity between theory and practice. Madrasah curriculum has a distinctive religions experienced difficulties in how religious subjects functioning integrative and relevant to the present conditions. Through literature review, it was found that the critical education can be used as an alternative in reconstructing the existing of madrasah curriculum. Critical education gives a basic framework and substantial how egalitarian, humanist education, and transformative it can be implemented. It is done with the four principles in the process of reconstruction of the madrasah’s curriculum, namely to minimize the gap between theory and practice in the sphere of organizing material, growing the awareness of educators and learners become critical educators and critical learners that achieved together, lead learners to realize the potential significantly, and the transmission of Islamic values through a hidden curriculum.Keywords: Madrasah Curriculum and Critical Education